Bladder morbidity and hepatic fibrosis in mixed Schistosoma haematobium and S. mansoni Infections: a population-wide study in Northern Senegal. - Lynn Meurs; Moustapha Mbow; Kim Vereecken; Joris Menten; Souleymane Mboup; Katja Polman (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: The global distribution map of schistosomiasis shows a large overlap of Schistosoma haematobium- and S. mansoni-endemic areas in Africa. Yet, little is known about the consequences of mixed Schistosoma infections for the human host. A recent study in two neighboring co-endemic communities in Senegal indicated that infection intensities of both species were higher in mixed than in single infections. Here, we investigated the relationship between mixed Schistosoma infections and morbidity in the same population. So far, this has only been studied in children. METHODS: Schistosoma infection was assessed by microscopy. Schistosoma-specific morbidity was assessed by ultrasound according to WHO guidelines. Multivariable logistic regression models were used to identify independent risk factors for morbidity. PRINCIPAL FINDINGS: Complete parasitological and morbidity data were obtained from 403 individuals. Schistosoma haematobium-specific bladder morbidity was observed in 83% and S. mansoni-specific hepatic fibrosis in 27% of the participants. Bladder morbidity was positively associated with S. haematobium infection intensity (OR = 1.9 (95% CI 1.3-2.9) for a 10-fold increase in intensity). Moreover, people with mixed infections tended to have less bladder morbidity than those with single S. haematobium infections (OR = 0.3 (95% CI 0.1-1.1)). This effect appeared to be related to ectopic S. mansoni egg elimination in urine. Hepatic fibrosis on the other hand was not related to S. mansoni infection intensity (OR = 0.9 (95% CI 0.6-1.3)), nor to mixed infections (OR = 1.0 (95% CI 0.7-1.7)). CONCLUSIONS/SIGNIFICANCE: This is the first population-wide study on the relationship between mixed Schistosoma infections and morbidity. Mixed infections did not increase the risk of S. mansoni-associated morbidity. They even tended to reduce the risk of S. haematobium-associated morbidity, suggesting a protective effect of S. mansoni infection on bladder morbidity. These unexpected results may have important consequences ...